Analisis Faktor Risiko Umur Kehamilan Ibu dan Jenis Persalinan terhadap Kejadian Asfiksia pada Bayi Baru Lahir di Kabupaten Mamuju - Dina Mariana; Ashriady Ashriady (Poltekkes Kemenkes Maluku, 2020)
One risk factor for asphyxia is maternal gestational age, at gestational age >42 weeks (post term), successful babies can increase asphyxia due to suboptimal placental function. The purpose of the study was to analyze the risk factors for gestational age and type of delivery for the incidence of asphyxia in newborns in Mamuju District Hospital and Regional Hospital in West Sulawesi Province. This type of research is an analytic study with a Case Control Study design. The study period was in August - September 2018. The case population was all infants questioned and accounted for asphyxia, control participants were all infants who were resisted and not covered at the Mamuju Regency Regional General Hospital and the West Sulawesi Provincial General Hospital. Large sample size = 36 and control sample = 72, with a ratio of 1: 2, the total sample size was 108 people, using purposive sampling technique. The results showed that mothers who changed the Sectio caesarea were 2,469 times risk of experiencing asphyxia in their newborns. Prevention needs to be done with the help of good knowledge for pregnant women when antenatal care about high risk with the action of Sectio Caesarea that can be done asphyxia.